THE ROLE OF LAPAROSCOPY IN THE MANAGEMENT OF PEDIATRIC APPENDICITIS (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis examines current evidence supporting laparoscopic intervention in children, analyzing diagnostic accuracy, surgical outcomes, and postoperative recovery patterns. Contemporary studies demonstrate reduced hospital length of stay, decreased wound infection rates, and improved cosmetic outcomes with laparoscopic techniques. The minimally invasive approach offers particular advantages in complex cases including perforated appendicitis and obese pediatric patients. Evidence supports the implementation of laparoscopic appendectomy as the preferred surgical method for pediatric appendicitis across all age groups and clinical presentations.